How Do University Students’ Perceptions of the Instructor’s Role Influence Their Learning Outcomes and Satisfaction in Cloud-Based Virtual Classrooms During the COVID-19 Pandemic? - Wang, Rong; Han, Jiying; Liu, Chuanyong; Xu, Hongji (Frontiers in Psychology, 2021)
This study examined the relationships between the role of the instructor and university students’ learning outcomes in cloud-based classrooms during the COVID-19 (coronavirus disease 2019) pandemic. The results of an online survey of 7,210 university students in mainland China revealed that the students’ perceived learning outcomes and learning satisfaction were positively related to instructor innovation and negatively related to instructor performance. Instructional support was positively related to the students’ perceived learning outcomes but not directly related to their learning satisfaction. The students’ academic self-efficacy mediated the influence of instructional support and instructor innovation on their perceived learning outcomes and learning satisfaction. The results contribute to knowledge of the role instructors play in facilitating students’ learning outcomes in higher education and suggest ways to improve the learning environment and learning outcomes, especially in cloud-based virtual classrooms.